An Infective Endocarditis Case Report Involving Both Native Aortic and Mitral Valves Due to Streptococcus Vestibularis - Döngelli, Hüseyin; Kızartıcı, Baver; Tarhan, Mustafa Oktay; Özpelit, Ebru; Sarıosmanoğlu, Osman Nejat; Taşçı, Hatice Kübra (Prague medical report, 2025)
Infective endocarditis (IE) is a life-threatening disease, with its mortality rate varying depending on the infectious agent. Streptococci are among the most common causes of infective endocarditis. However, Streptococcus vestibularis has rarely been associated with human infections, typically affecting patients with underlying conditions such as immunosuppressive diseases, valve replacement, rheumatic heart disease, and hemodialysis. We present the case of a 26-year-old man who presented with fever, unanticipated weight loss, and fatigue. Although no typical risk factors for infective endocarditis were identified at admission, transesophageal echocardiography revealed a bicuspid aortic valve with calcification, paravalvular aortic abscess formation, and vegetations on the anterior leaflet of the mitral valve. Blood cultures grew S. vestibularis, which was initially sensitive to benzylpenicillin but developed emergent resistance on the third day of the antibiotic treatment. Subsequently, ceftriaxone therapy was initiated, and blood cultures became sterile on day 10. The patient eventually underwent aortic valve replacement. We report the first known case of native aortic and mitral valve endocarditis caused by S. vestibularis, accompanied by a paravalvular abscess around the native aortic valve, in a patient who had no typical risk factors for infective endocarditis, except for a bicuspid aortic valve.
Keywords: mitrální chlopeň; bikuspidální aortální chlopeň; Aortic Valve Insufficiency; Male; Endocarditis, Bacterial; penicilin G; streptokokové infekce; Bicuspid Aortic Valve Disease; antibakteriální látky; Heart Valve Prosthesis Implantation; Adult; Ceftriaxone; dospělí; cefalosporiny třetí generace; mužské pohlaví; chirurgická náhrada chlopně; aortální insuficience; Penicillin G; Streptococcal Infections; lidé; Anti-Bacterial Agents; ceftriaxon; Humans; bakteriální endokarditida; Third Generation Cephalosporins; rezistence na penicilin; Penicillin Resistance; Mitral Valve